2013
DOI: 10.1111/jphp.12055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herbal supplements on the bioactivation of chemotherapeutic agents

Abstract: Commercially available supplements are widely used by patients and their potential impact on the efficacy of the chemotherapy is often unknown. The clinical significance of these results needs to be evaluated in a comprehensive clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Clinical studies found ginger as effective and safe to prevent pregnancy-associated nausea and vomiting ( Borrelli et al, 2005 ; Ding et al, 2013 ). In human liver microsomes, the hydroethanolic extract inhibited CYP2C19 and CYP2D6 ( Kim et al, 2012 ; Gorman et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies found ginger as effective and safe to prevent pregnancy-associated nausea and vomiting ( Borrelli et al, 2005 ; Ding et al, 2013 ). In human liver microsomes, the hydroethanolic extract inhibited CYP2C19 and CYP2D6 ( Kim et al, 2012 ; Gorman et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…SJW has been described through several studies as an HMP product that can lead in clinically significant PK and PD interactions [54,55,56]. Especially for SJW, the underlying pharmacological mechanisms of the PK and PD interactions have been described in detail [57,58]. SJW contain different groups of compounds such as hypericin, hyperforin, and flavonoids.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to St John's wort and ginger root extract, black cohosh was the strongest inhibitor for both CYP and carboxylesterase-mediated biotransformation of tamoxifen and irinotecan, respectively, to their active metabolites (Gorman et al, 2013). The clinical significance of these results needs to be evaluated in a comprehensive clinical trial.…”
Section: Adverse Effects and Safetymentioning
confidence: 99%